2018
DOI: 10.1016/j.envint.2018.10.055
|View full text |Cite
|
Sign up to set email alerts
|

Metals and oxidative potential in urban particulate matter influence systemic inflammatory and neural biomarkers: A controlled exposure study

Abstract: Background: Oxidative stress and inflammation are considered to be important pathways leading to particulate matter (PM)-associated disease. In this exploratory study, we examined the effects of metals and oxidative potential (OP) in urban PM on biomarkers of systemic inflammation, oxidative stress and neural function. Methods: Fifty-three healthy non-smoking volunteers (mean age 28 years, twenty-eight females) were exposed to coarse (2.5–10 μm, mean 213 μg/m3), fine (0.15–2.5 μm, 238 μg/m3), and/or ultrafin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 45 publications
5
33
0
Order By: Relevance
“…In a study assessing the short-term oxidative potential of urban particulate matter in adult nonsmoking volunteers, several metals present in coarse, fine, and ultrafine PM (including Ba, Cu, Ni, and V) were significantly associated with increased levels of biomarkers of systemic inflammation, oxidative stress, and neural function. Ba, in particular, induced a significant increment (+11% at 1 h, +14% at 21 h postexposure) of L1(UCHL1) (traumatic brain injury marker ubiquitin C-terminal hydrolase L1); Cu exposure increased (+14% at 1 h) levels of the DNA oxidation marker 8-hydroxy-deoxy-guanosine; urinary cortisol increased by 88% after exposure to V, and the blood inflammatory marker VEGF (vascular endothelia growth factor) increased by 5.3% 1 h after Ni exposure [80].…”
Section: Discussionmentioning
confidence: 99%
“…In a study assessing the short-term oxidative potential of urban particulate matter in adult nonsmoking volunteers, several metals present in coarse, fine, and ultrafine PM (including Ba, Cu, Ni, and V) were significantly associated with increased levels of biomarkers of systemic inflammation, oxidative stress, and neural function. Ba, in particular, induced a significant increment (+11% at 1 h, +14% at 21 h postexposure) of L1(UCHL1) (traumatic brain injury marker ubiquitin C-terminal hydrolase L1); Cu exposure increased (+14% at 1 h) levels of the DNA oxidation marker 8-hydroxy-deoxy-guanosine; urinary cortisol increased by 88% after exposure to V, and the blood inflammatory marker VEGF (vascular endothelia growth factor) increased by 5.3% 1 h after Ni exposure [80].…”
Section: Discussionmentioning
confidence: 99%
“…In total 58 studies were identified exploring both the OP and biological effects of PM and/or combustion particles in cells, animals or humans [27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84]. Among these were three cases of multiple studies based on the same particle samples and measurements of OP: Two studies on in vitro and in vivo effects of a set of wood smoke and PM samples [45,46], and six studies from a series of PM exposures of human volunteers under the RAPTES (Risk of Airborne Particles: A Toxicological–Epidemiological Hybrid Study) project [67,68,69,70,71,72], and three epidemiolo...…”
Section: Literature Search and Selection Of Studiesmentioning
confidence: 99%
“…Metal ions, non-metallic anions, and their inorganic derivatives (oxides, salts, etc. ) are among the PM constituents (Brito et al, 2018;Meng et al, 2013;Popoola et al, 2018) which are considered to be co-responsible for PM toxicity, likely because of the oxidative stress which several chemical species may induce in cellular tissues (Meng et al, 2013;Liu et al, 2018;Yang et al, 2019). If PM is in contact with environmental or physiological solutions, the substances contained in the particles may be released, thus becoming bio-accessible and potentially toxic to living organisms and human tissues.…”
Section: Introductionmentioning
confidence: 99%